The Role of Human Capital in Science, Technology and Innovation - Dzhamilya Abuzyarova; Veronika Belousova; Zhaklin Krayushkina; Yuliya Lonshchikova; Ekaterina Nikiforova; Nikolay Chichkanov (Foresight and STI Governance, 2019)
As a result of the transformation of the labor market, the constant development of human capital has become crucial. This paper considers the role of human capital in professional development through the prism of 16 semi-structured interviews with both Russian and foreign graduates of a master’s program focused on training experts in the field of science, technology, and innovation. Most of the graduates of the program found jobs in the corporate sector and at research centers, but among the interviewees, there were also representatives who chose self-employment or public service. The contribution of undergraduate and master’s degrees to the professional development of these interviewees was assessed and they noted that if studying at the undergraduate level contributed primarily to obtaining subject knowledge, then studying at the master’s level contributed to the development of missing competencies and the opening of new professional opportunities. Interviewees identified emotional and social intelligence as key skills in their professional development and noted the critical importance of digital skills and subject knowledge. In turn, the most popular way of training, in the opinion of respondents, is online education.